IMPLEMENTATION OF KAHOOT APPLICATION AS A STRATEGY TO GROW THE SPIRIT OF COMPETITION FOR STUDENTS - I Kadek Agus Bisena (Journal of Language, Literature and Teaching, 2020)
STMIK STIKOM Indonesia students are millennials who are literate with technology. Kahoot is a game platform in Education that is based online is one way to increase student motivation in learning English. This popular learning media will be tested on students on the final agenda in each meeting session. This application can not only be done in classroom learning, but in the process of live sessions in online learning or e-learning. This study will use a qualitative descriptive analysis of the implementation of Kahoot at the end of the session, which aims to find out whether the Kahoot platform is able to increase the motivation of students to compete in learning English, and how the process of implementing the game in the classroom and in live sessions.